The role of CXCR4 in highly malignant human gliomas biology: Current knowledge and future directions. Issue 7 (8th April 2014) - Gagliardi, Filippo; Narayanan, Ashwin; Reni, Michele; Franzin, Alberto; Mazza, Elena; Boari, Nicola; Bailo, Michele; Zordan, Paola; Mortini, Pietro
<x xml:space="preserve">Abstract</x> Given the extensive histomorphological heterogeneity of high‐grade gliomas, in terms of extent of invasiveness, angiogenesis, and necrosis and the poor prognosis for patients despite the advancements made in therapeutic management. The identification of genes associated with these phenotypes will permit a better definition of glioma heterogeneity, which may ultimately lead to better treatment strategies. CXCR4, a cell surface chemokine receptor, is implicated in the growth, invasion, angiogenesis and metastasis in a wide range of malignant tumors, including gliomas. It is overexpressed in glioma cells according to tumor grade and in glioma tumor initiating cells. There have been various reports suggesting that CXCR4 is required for tumor proliferation, invasion, angiogenesis, and modulation of the immune response. It may also serve as a prognostic factor in characterizing subsets of glioblastoma multiforme, as patients with CXCR4‐positive gliomas seem to have poorer prognosis after surgery. Aim of this review was to analyze the current literature on biological effects of CXCR4 activity and its role in glioma pathogenesis. A better understanding of CXCR4 pathway in glioma will lead to further investigation of CXCR4 as a novel putative therapeutic target. GLIA 2014;62:1015–1023